2021
DOI: 10.1039/d1ma00906k
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced electronic and ionic effects in strontium titanate

Abstract: The interaction of light with solids has been of ever-growing interest for centuries, even more so since the quest for sustainable utilization and storage of solar energy became a major...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 382 publications
(717 reference statements)
0
9
0
Order By: Relevance
“…A promising photocatalyst that is widely used for generating clean energy is the perovskite oxide SrTiO3. [9][10][11][12] Domen et al…”
Section: Introductionmentioning
confidence: 99%
“…A promising photocatalyst that is widely used for generating clean energy is the perovskite oxide SrTiO3. [9][10][11][12] Domen et al…”
Section: Introductionmentioning
confidence: 99%
“…A promising photocatalyst that is widely used for generating clean energy is the perovskite oxide SrTiO 3 . [9][10][11][12] Domen et al reported that Al-doped SrTiO 3 (Al-SrTiO 3 ) is an excellent photocatalyst for efficient photocatalytic H 2 O splitting, 13 where it showed a near 100% internal quantum efficiency. This efficiency was attributed to the particle shape of the photocatalyst, which promotes charge separation, as evidenced by an electrical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Solid solutions of the perovskite family Sr(Ti,Fe)O 3−y are important due to their ability to vary their physical and chemical properties with composition, iron valence state, and oxygen nonstoichiometry. These can determine the material's transport, 1 electronic, 2 magnetic 3,4 and optical 5,6 properties, crucial for applications in electrochemical devices, 7 such as electrodes for solid oxide fuel [8][9][10] and photoelectrochemical cells, 11,12 oxygen sensors, 13,14 synaptic transistors 15,16 or memristive devices, [17][18][19] Fig. 1 and review in ref.…”
Section: Introductionmentioning
confidence: 99%